Cultural Communication and Digital Mnemonic Practices: The Case of Orang Sungai in Urban Pontianak, Indonesia - Annisa Dwi Lestari; Muhammad Maulana; Nur Quma Laila; Mirna Yusuf (INJECT (Interdisciplinary Journal of Communication), 2026)
This study aims to analyze how the Orang Sungai community in Pontianak, Indonesia, reproduces identity through cultural communication channels and digital platforms. Amid increasingly intensive pressures of urbanization, the local identity of riparian communities is often marginalized by formal development narratives that overlook the cultural dimensions of riverbank life. Using an interpretive qualitative approach to narrative texts and digital representations, this study finds that identity communication is articulated through three main domains, namely the use of river cosmology as a moral anchor of communication, the conversion of water-based work ethics into economic-communicative resilience, and mnemonic practices through digital commemoration. The findings show that adaptive cultural communication enables the community to negotiate its presence in urban public space without losing the ecological roots of its identity. This study recommends the integration of riparian local wisdom into urban development communication policy.